Is it possible to predict atherosclerosis in the ascending aorta by the patient’s lipid panel? - Haberal, İsmail (Arch Med Sci Atheroscler Dis, 2020)
INTRODUCTION: Atherosclerosis is a chronic inflammatory event characterized by stiffness and thickening of the vascular walls. In our daily practice, we assume the atherosclerotic potential of the patient by following the total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL) and triglyceride levels (lipid panel). We aimed to understand the relation between the HDL, LDL, cholesterol levels and the atherosclerosis in large vascular structures such as the ascending aorta. MATERIAL AND METHODS: We have searched for atherosclerosis in the aortic tissue samples from 48 patients. It is a study in which we examine the correlation of preoperative cholesterol values (HDL, LDL, triglyceride, total cholesterol) by dividing the patients into two groups according to the presence of plaque. RESULTS: Forty-three (89.6%) male and 5 (10.4%) female patients between 39 and 81 years of age were included in the study. There was no statistically significant difference between the patients’ preoperative cardiovascular risk assessments. The free T3 values were within the normal range in all patients, but there was a difference that patients in the non-atherosclerosis group had lower values. There was no statistically significant difference between the two groups’ HDL, LDL, total cholesterol, or triglyceride parameters. CONCLUSIONS: As a result, in our study, no significant difference was found between HDL-C, LDL-C, triglyceride, total cholesterol values and the pathological process of aortic atherosclerosis. As a result of this study, we believe that it was necessary to correct the error margins of these parameters. In addition, it required the need for a clearer laboratory parameter to demonstrate atherosclerosis.